Exploring The Practices Of English Village (A Case Study at Nyayum Village) - Pitiana, Pitiana; Aunurrahman, Aunurrahman; Sahrawi, Sahrawi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This research is descriptive qualitative which aims to find out the practices of the English village in the village of Nyayum. A class consists of eighteen participants from different classes who are deliberately selected as samples. Data was collected by using observation, field notes and student text. This research was conducted during teaching and learning activities. This research lasted for eight meetings. In teaching and learning activities, four stages of genre pedagogy are applied, namely knowledge building, modeling, combined joint construction, and independent construction. The application of a Genre-Based Approach to help Students to be able to communicative. Communicative can be in the form of oral, written, or even nonverbal. It is an inclusive term that refers to having knowledge of the language as well as the skills to use language in real-life situations to meet communicative needs. Language according to the researcher, is achievement in communication. During teaching and learning activities, observations were made by collecting field notes and student text. data analysis used thematic analysis to analyze field notes and text documents therefore, trigulation was carried out to validate the data. the findings describe the practice of English village at  nyayum village using a genre-based approach in learning activities. The practice of English village using a genre based approach as a method in teaching and learning activities can help students practice English because there is interaction between tutors, and participants. So, it can be used to teach English both informal and non-formal education.